25-year cycle evolution theory: relationship between German economic development mode and human resource management innovation after World War II. (14th October 2021) - Lin, Xinqi; Shi, Jiawei
After the Second World War, Germany created the economic miracle by improve its economic development model, triggered many rounds of climax of management innovation. In 2011, some scholars proposed the 25-year cycle evolution theory. This paper review and analyses the German transformation of economic development mode and the history of the human resources management innovation in the last century. Then the study finds out the periodic features in the Germany case and deduces the 25-year cycle evolution theory and its role of the transmission mechanism. Finally, to represent the level of human resources management innovation, the study process the data of IMD World Talent Report conducted by International Institute for Management Development, and generated the human resources management innovation index. Moreover, to represent its economic development level, the study generates the GDP growth rate conversion index from the German historical GDP data. Meanwhile, the applied statistical test analysed the volatility characteristics and causation relationship between economic development and human resources management innovation. The empirical analysis also predicts the development trend in the future and verifies the rationality of the 25-year cycle evolution theory, and provides a solid mathematical foundation for further enriching the theory and its hypothesis.